Life of Pi : a novel - Martel, Yann (Boston : Mariner Books/Houghton Mifflin Harcourt, 2001)
After the sinking of a cargo ship, a solitary lifeboat remains bobbing on the wild blue Pacific. The only survivors from the wreck are a sixteen-year-old boy named Pi, a hyena, a wounded zebra, an orangutan, and a 450-pound Royal Bengal tiger.
Keywords: Shipwreck survival -- Fiction; Survival at sea -- Fiction; Human-animal relationships -- Fiction; Storytelling -- Fiction; Teenage boys -- Fiction; Ocean travel -- Fiction; Zoo animals -- Fiction; Orphans -- Fiction; Tiger -- Fiction; Pacific Ocean -- Fiction; Psychological fiction; Adventure fiction